Hip Abductor Muscle Strength Deficit as a Risk Factor for Inversion Ankle Sprain in Male College Soccer Players: A Prospective Cohort Study. Issue 7 (26th July 2021) - Kawaguchi, Kohei; Taketomi, Shuji; Mizutani, Yuri; Inui, Hiroshi; Yamagami, Ryota; Kono, Kenichi; Takagi, Kentaro; Kage, Tomofumi; Sameshima, Shin; Tanaka, Sakae; Haga, Nobuhiko
Background: Previous studies have attempted to determine whether certain risk factors can predict the occurrence of inversion ankle sprains in male collegiate soccer players. However, no consensus has been reached on the predictive risk factors of inversion ankle sprain in this population. Purpose: To identify risk factors for inversion ankle sprains among male collegiate soccer players. Study Design: Cohort study; Level of evidence, 2. Methods: Included were 145 male collegiate soccer players in Japan who were assessed during a preseason medical checkup for potential risk factors of inversion ankle sprain. The preseason assessment included anthropometric measurements, joint laxity and flexibility, muscle flexibility, muscle strength, and balance ability, with a total of 33 variables. The participants were monitored during the 2019 season for inversion ankle sprains as diagnosed by physicians. Results: A total of 31 inversion ankle sprains in 31 players (21.4%) occurred during the season. Only the measured isometric hip abductor strength was significantly lower in injured players as compared with uninjured players. Logistic regression analysis revealed measured hip abductor muscle strength deficit as a significant risk factor for inversion ankle sprain (odds ratio, 0.978 [95% CI, 0.976-0.999]; P = .05). Conclusion: Hip abductor strength deficit was a risk factor for inversion ankle sprain in the study population. This finding could be useful for the prevention of inversion ankle sprains in male collegiate soccer players.